Techno-economic comparison of centralized versus decentralized biorefineries for two alkaline pretreatment processes. (February 2017) - Stoklosa, Ryan J.; del Pilar Orjuela, Andrea; da Costa Sousa, Leonardo; Uppugundla, Nirmal; Williams, Daniel L.; Dale, Bruce E.; Hodge, David B.; Balan, Venkatesh
Highlights: A techno-economic analysis (TEA) compared two biorefinery processing scenarios. Decentralized biorefineries employing AFEX require the highest capital cost. A centralized biorefinery using AHP has lower capital cost but higher water use. The best-case AFEX scenario yields the lowest minimum ethanol selling price (MESP). Biomass cost and alkali recovery exert a significant impact on MESPs. Abstract: In this work, corn stover subjected to ammonia fiber expansion (AFEX™) 1 pretreatment or alkaline pre-extraction followed by hydrogen peroxide post-treatment (AHP pretreatment) were compared for their enzymatic hydrolysis yields over a range of solids loadings, enzymes loadings, and enzyme combinations. Process techno-economic models were compared for cellulosic ethanol production for a biorefinery that handles 2000 tons per day of corn stover employing a centralized biorefinery approach with AHP or a de-centralized AFEX pretreatment followed by biomass densification feeding a centralized biorefinery. A techno-economic analysis (TEA) of these scenarios shows that the AFEX process resulted in the highest capital investment but also has the lowest minimum ethanol selling price (MESP) at $2.09/gal, primarily due to good energy integration and an efficient ammonia recovery system. The economics of AHP could be made more competitive if oxidant loadings were reduced and the alkali and sugar losses were also decreased.